Research data supporting 'Cracked equivalent beam models for assessing tunnelling-induced damage in masonry buildings' - Acikgoz, M (University of Oxford, 2020)
The MATLAB source files (.fig) of the figures in the cited publication (accepted for publication in the ASCE Journal of Geotechnical and Geoenvironmental Engineering) can be found in this dataset.